Perioperative taurine or taurolidine supplementation on clinical outcomes: A systematic review with meta-analysis - Ho, Kwok M.; Harahsheh, Yusra (ANESTHESIOLOGY AND PERIOPERATIVE SCIENCE, 2024)
Taurine is a conditionally essential amino acid that has been reported to have antioxidative and immunomodulatory effects either directly or through its interactions with gut microbiome. Although taurine has been widely used as a health supplement and also for treatment of congestive heart failure in Japan, its roles in the perioperative setting have not been well characterized. The purpose of this systematic review and meta-analysis was to assess whether oral or intravenous taurine, or its derivatives such as taurolidine, can offer benefits compared to placebo in the perioperative setting. Non-randomized studies, trials assessed topical taurine or taurolidine, or trials did not report clinical outcomes were excluded. Six randomized-controlled-trials (RCTs) involving a total of 596 adult surgical patients, in PubMed, MEDLINE and EMBASE databases on September 14, 2023 were identified and meta-analyzed using a fixed-effect model. Biases were assessed by reporting individual trial elements. Taurine or taurolidine (which is readily metabolized by hydrolysis to taurine) supplementation was associated with a reduction in all-cause infection (5 trials: pooled odds ratio (OR) 0.59; 95% confidence interval (CI) 0.38–0.92; p = 0.020) but not delirium (2 trials: OR 0.63, 95% CI 0.38–1.04; p = 0.071) or mortality (4 trials: OR 0.82, 95% CI 0.43–1.58; p = 0.557) compared to placebo. Using the ‘trim and fill’ technique to adjust for publication bias did not change the favorable effect of taurine on risk of infection (OR 0.61, 95% CI 0.40–0.95). Because the number of studies included was small, the promising benefits of taurine on risks of perioperative infection should be confirmed by adequately-powered RCTs.